Novel de novo missense mutation in the interferon regulatory factor 6 gene in an Italian infant with IRF6-related disorder - Ingrid Anne Mandy Schierz; Salvatore Amoroso; Vincenzo Antona; Mario Giuffrè; Ettore Piro; Gregorio Serra; Giovanni Corsello (BMC, 2022)
Abstract Background Congenital maxillomandibular syngnathia is a rare craniofacial anomaly leading to difficulties in feeding, breathing and ability to thrive. The fusion may consist of soft tissue union (synechiae) to hard tissue union. Isolated cases of maxillomandibular fusion are extremely rare, it is most often syndromic in etiology. Case presentation Clinical management of a female newborn with oromaxillofacial abnormities (synechiae, cleft palate, craniofacial dysmorphisms, dental anomaly) and extraoral malformations (skinfold overlying the nails of both halluces, syndactyly, abnormal external genitalia) is presented. The associated malformations addressed to molecular genetic investigations revealing an interferon regulatory factor 6 (IRF6)-related disorder (van der Woude syndrome/popliteal pterygium syndrome). A novel de novo heterozygous mutation in exon 4 of IRF6 gene on chromosome 1q32.2, precisely c.262A > G (p.Asn88Asp), was found. Similarities are discussed with known asparagine missense mutations in the same codon, which may alter IRF6 gene function by reduced DNA-binding ability. A concomitant maternal Xp11.22 duplication involving two microRNA genes could contribute to possible epigenetic effects. Conclusions Our reported case carrying a novel mutation can contribute to expand understandings of molecular mechanisms underlying synechiae and orofacial clefting and to correct diagnosing of incomplete or overlapping features in IRF6-related disorders. Additional multidisciplinary evaluations to establish the phenotypical extent of the IRF6-related disorder and to address family counseling should not only be focused on the surgical corrections of syngnathia and cleft palate, but also involve comprehensive otolaryngologic, audiologic, logopedic, dental, orthopedic, urological and psychological evaluations.